PKA’s team building stronger together: building bonds, boosting success - Hambali, Satira; Raja Mohd Noor, Raja Nor Husna; Yunus, Juzailah Nur; Abdul Hamid, Mohd Samsudin; Musir, Adhilla Ainun; Abdul Karim, Nurulzatushima; Abdul Wahab, Kamsiah; Mohtar, Zul Azmi; Endut, Zaini; Hassan, Siti Hafizan; Ng, Kok Shien; Ahmad, Suzana; et al. (Unit Penerbitan PKAPP, 2025)
PKA’s Team Building 2024 was successfully held at Sedim Riverside Resort, Karangan, Kedah on July 10 - 11, 2024. This Team Building program involved 85 staff members from the Civil Engineering Faculty, UiTM Permatang Pauh, consisting of lecturers, assistant engineers, and laboratory assistants. The two-day program was conducted with these objectives in mind: i. To increase awareness of the importance of each individual's role in the faculty. ii. To foster a sense of responsibility among members for both their individual and group tasks. iii. To instill a sense of mutual respect among members when carrying out tasks and responsibilities. iv. To create a cheerful and productive working environment to achieve the organization's goals. Prior to the program, all staff members were divided into four teams (red, blue, green, and yellow). The team building activities on the first day began as early as 9:00 a.m. with a briefing session by Dr. Mohd Samsudin Abdul Hamid, who explained the objectives and rules for each game, followed by an aerobics session conducted by Cik Nurul Shahila Shahri Azhar from Sedim Riverside Resort. The games that were held during the morning session included Tarantula, Tuju Tin, and Ceboq Ayaq Sungai, while the Football Dart was held in the afternoon session. In the evening, after maghrib prayers, there was recitation of Yasin led by Dr. Anas Ibrahim, followed by a ‘tazkirah’, also by Dr Anas. After that, traditional games such as Batu Seremban, Tutup Botol, and Dam Aji were held. On the second day, the activities began with a Treasure Hunt and concluded with the prize-giving session. The Blue Team, led by Ir. Dr. Mohd Ashaari Masrom, emerged as the overall champion of the Team Building event.